2020
DOI: 10.7150/ijms.46910
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Transcriptome Profiling of Peripheral Blood Mononuclear Cells from Patients with Sepsis

Abstract: Background: Sepsis, as a clinical emergency, usually causes multiorgan dysfunction and can lead to high mortality. Establishment of specific and sensitive biomarkers for early diagnosis is critical to identify patients who would benefit from targeted therapy. In this study, we investigated this syndrome by analyzing the transcriptome of peripheral blood mononuclear cells (PBMCs) from patients with sepsis and identified sepsis-specific biomarkers. Methods: In this study, a total of 87 patients with sepsis and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
(33 reference statements)
4
4
0
Order By: Relevance
“…As previously described by Chen et al in a sepsis mouse model [ 25 ], we demonstrated that 3 h after injection, lipopolysaccharides promote inflammatory pathways in the hearts of young rats with the increase in genes involved in the regulation of NF-κB signaling. Reinforcing this observation, genes involved in the MAPK, mTOR, TLR2/MyD88 and JAK/STAT pathway are also up-regulated in the LPS group, as recently described in sepsis patients [ 26 ], confirming the pertinence of such approaches. JAK/STAT3 is a major pathway described as cardio-protective [ 27 , 28 ]; however, this pathway could also contribute to cardiac dysfunction [ 29 , 30 , 31 ], notably during septic shock [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 77%
“…As previously described by Chen et al in a sepsis mouse model [ 25 ], we demonstrated that 3 h after injection, lipopolysaccharides promote inflammatory pathways in the hearts of young rats with the increase in genes involved in the regulation of NF-κB signaling. Reinforcing this observation, genes involved in the MAPK, mTOR, TLR2/MyD88 and JAK/STAT pathway are also up-regulated in the LPS group, as recently described in sepsis patients [ 26 ], confirming the pertinence of such approaches. JAK/STAT3 is a major pathway described as cardio-protective [ 27 , 28 ]; however, this pathway could also contribute to cardiac dysfunction [ 29 , 30 , 31 ], notably during septic shock [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 77%
“…Examples include the use of a single gene, IFI27, which has a high diagnostic ability to differentiate between viral and bacterial pneumonia, with analysis of transcriptomic response signatures in sepsis. [10][11][12] The second approach is to use open access databases to further integrate data-driven artificial intelligence techniques into unscripted analyses and apply this to early prediction, prognostication, and mortality risk. The third approach is to combine individual transcriptomics data to complement other patient specific information.…”
Section: Transcriptomics In the Intensive Care Unitmentioning
confidence: 99%
“…The complexity of sepsis arises from its heterogeneity, with diverse clinical manifestations ranging from systemic inflammatory response to severe septic shock and multiple organ dysfunction syndrome [ 6 , 7 ]. Dysregulation of immune responses plays a central role in the pathophysiology of sepsis, and peripheral blood mononuclear cells (PBMCs) play a key role in this process [ 8 10 ]. Cells, including monocytes, lymphocytes, and dendritic cells, play important roles in balancing pro-inflammatory and anti-inflammatory responses [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%